Limit cycle oscillations at the L–I–H transition in TJ-II plasmas: triggering, temporal ordering and radial propagation. (30th April 2015) - Estrada, T.; Ascasíbar, E.; Blanco, E.; Cappa, A.; Castejón, F.; Hidalgo, C.; van Milligen, B.Ph.; Sánchez, E.
Abstract: The spatiotemporal evolution of the interaction between turbulence and flows has been studied close to the L–H transition threshold conditions in the edge of TJ-II plasmas. As in other devices the temporal dynamics of the interaction displays limit cycle oscillations (LCO) with a characteristic predator–prey relationship between flows and turbulence. At TJ-II, the turbulence-flow front is found to propagate radially outwards at the onset of the LCO and in some particular cases, after a short time interval without oscillations, a reversal in the front propagation velocity is observed. Associated to this velocity reversal, a change in the temporal ordering of the LCO is measured. However, the change in the temporal ordering is not related to an intrinsic change in the nature of the LCO. In all cases the turbulence increase leads the process and produces an increase in the E  ×  B flow shear. Dedicated experiments have been carried out to investigate the physical mechanisms triggering the onset of the LCO. At TJ-II the LCO are preferentially observed close to the transition threshold conditions at specific magnetic configurations having a low order rational surface located at the inner side of the E  ×  B flow shear location. The behaviour of different frequency modes has been analysed and interpreted in terms of a geodesic acoustic mode generated by the non-linear mode coupling of Alfvén eigenmodes that evolves towards a low frequency flow, plus a MHD mode linked to the low order rational surface, as precursors of the LCO.